2020
DOI: 10.1182/blood.2019002300
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell-directed therapies in monoclonal gammopathy-associated scleromyxedema

Abstract: Scleromyxedema is a rare skin and systemic mucinosis that is usually associated with monoclonal gammopathy (MG). In this French, multicenter, retrospective study of 33 patients, we investigated the clinical and therapeutic features of MG-associated scleromyxedema. Skin molecular signatures were analyzed using a transcriptomic approach. Skin symptoms included papular eruptions (100%), sclerodermoid features (91%), and leonine facies (39%). MG involved an IgG isotype in all patients, with a predominant λ light c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(61 citation statements)
references
References 40 publications
2
55
0
4
Order By: Relevance
“…8 Similarly, a retrospective study of 33 scleromyxedema patients showed corticosteroids alone (0.75 mg/kg/day of equivalent prednisone) was successful in only 1 patient out of 3 total. 7 This was similar to our patient as he had treatment failure with oral prednisone alone. Due to its ineffectiveness alone, glucocorticoids are more often used in conjunction with other treatment regimens such as melphalan, methotrexate, thalidomide, hydroxychloroquine, cyclophosphamide, and bortezomib.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…8 Similarly, a retrospective study of 33 scleromyxedema patients showed corticosteroids alone (0.75 mg/kg/day of equivalent prednisone) was successful in only 1 patient out of 3 total. 7 This was similar to our patient as he had treatment failure with oral prednisone alone. Due to its ineffectiveness alone, glucocorticoids are more often used in conjunction with other treatment regimens such as melphalan, methotrexate, thalidomide, hydroxychloroquine, cyclophosphamide, and bortezomib.…”
Section: Discussionsupporting
confidence: 86%
“…The course of scleromyxedema is unpredictable, especially due to the variable response to treatment and the high relapse rate after cessation of treatment. The overall survival rate at 3 years was reported to be 97% in a recent retrospective study, 7 which is an improvement compared to 76.2% in a previous study 8 …”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…In der Literatur ist nur ein Bericht einer Spontanhei lung zu finden [24]. In einer Studie von Rongioletti und Merlo et al [17] [36,37] 2 [17,47] 5 [40,41,[57][58][59] 14 [60][61][62][63][64][65][66][67][68][69][70][71][72][73] -in Kombination 0 0 3 [17,38,47] 0 17 [46,48,49,55,[74][75][76][77][78][79][80][81][82][83][84][85][86] Systemische Kortikosteroide 0 0 2 [17,38] 1 [87] 8 [71,[88][89]…”
Section: Systembeteiligung Und Verlaufunclassified